Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Pre-diagnosis neutrophil-to-lymphocyte ratio and mortality in individuals who develop lung cancer - Laurie Grieshober; Stefan Graw; Matt J. Barnett; Gary E. Goodman; Chu Chen; Devin C. Koestler; Carmen J. Marsit; Jennifer A. Doherty (Cancer Causes & Control, 2021)
Purpose The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that has been reported to be associated with survival after chronic disease diagnoses, including lung cancer. We hypothesized that the inflammatory profile reflected by pre-diagnosis NLR, rather than the well-studied pre-treatment NLR at diagnosis, may be associated with increased mortality after lung cancer is diagnosed in high-risk heavy smokers. Methods We examined associations between pre-diagnosis methylation-derived NLR (mdNLR) and lung cancer-specific and all-cause mortality in 279 non-small lung cancer (NSCLC) and 81 small cell lung cancer (SCLC) cases from the β-Carotene and Retinol Efficacy Trial (CARET). Cox proportional hazards models were adjusted for age, sex, smoking status, pack years, and time between blood draw and diagnosis, and stratified by stage of disease. Models were run separately by histotype. Results Among SCLC cases, those with pre-diagnosis mdNLR in the highest quartile had 2.5-fold increased mortality compared to those in the lowest quartile. For each unit increase in pre-diagnosis mdNLR, we observed 22–23% increased mortality (SCLC-specific hazard ratio [HR] = 1.23, 95% confidence interval [CI]: 1.02, 1.48; all-cause HR = 1.22, 95% CI 1.01, 1.46). SCLC associations were strongest for current smokers at blood draw (Interaction P s = 0.03). Increasing mdNLR was not associated with mortality among NSCLC overall, nor within adenocarcinoma ( N = 148) or squamous cell carcinoma ( N = 115) case groups. Conclusion Our findings suggest that increased mdNLR, representing a systemic inflammatory profile on average 4.5 years before a SCLC diagnosis, may be associated with mortality in heavy smokers who go on to develop SCLC but not NSCLC.

Allergies and risk of head and neck cancer - Dominique S. Michaud; Scott M. Langevin; Melissa Eliot; Heather H. Nelson; Michael D. McClean; Brock C. Christensen; Carmen J. Marsit; Karl T. Kelsey (Cancer Causes & Control, 2012)

Association of secondhand smoke exposures with DNA methylation in bladder carcinomas - Charlotte S. Wilhelm-Benartzi; Brock C. Christensen; Devin C. Koestler; E. Andres Houseman; Alan R. Schned; Margaret R. Karagas; Karl T. Kelsey; Carmen J. Marsit (Cancer Causes & Control, 2011)

Bladder cancer SNP panel predicts susceptibility and survival - Angeline S. Andrew; Jiang Gui; Arthur C. Sanderson; Rebecca A. Mason; Elaine V. Morlock; Alan R. Schned; Karl T. Kelsey; Carmen J. Marsit; Jason H. Moore; Margaret R. Karagas (Human Genetics, 2009)